Peran Pendidikan Agama Islam dalam Membentuk Karakter Siswa di Era Digital - Arifuddin Arifuddin; Nelfa Yosi; Marlina Marlina (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
This study aims to examine the role of Islamic education in shaping the characters of students in the digital era. The study involves a literature review by exploring research findings and relevant articles, and identifying implications for the field of education. The results indicate that Islamic education plays a significant role in shaping the characters of students in the digital era. In the context of the digital era, Islamic education not only teaches religious values but also involves the learning of ethics and morality for students. This study reveals that Islamic education can teach students about moral values, develop digital ethics, and foster spiritual awareness in the use of technology. The implications of this study include curriculum development that encompasses ethical and moral aspects of technology use, teacher training in teaching digital ethics and responsible technology use, and partnerships with parents in shaping students' characters in the digital era. This research is important to be known and understood by educational institutions and teachers so they can develop effective strategies in shaping responsible, ethical, and integrity-based characters of students in this digital era. In a connected and digitalized era, it is crucial to integrate Islamic moral and ethical values into education to enable students to use technology wisely and responsibly.